Whole Organism Genome Editing: Targeted Large DNA Insertion via ObLiGaRe Nonhomologous End-Joining in Vivo Capture. Issue 9 (1st September 2015) - Yamamoto, Yutaka; Bliss, Jacob; Gerbi, Susan A
Abstract: Targeted gene insertion is a goal of genome editing and has been performed in cultured cells but only in a handful of whole organisms. The existing method to integrate foreign DNA using the homologous recombination pathway is inherently low efficiency, and many systems are refractory to this method. Several additional manipulations have been developed to gain greater efficiency by suppressing the competing dominant repair pathway of nonhomologous end-joining. However, this can be laborious and in practice limits the range of hosts where the method is applicable. Here, we use the preferred pathway of nonhomologous end-joining (used previously to create indels for gene inactivation) for precise integration of large DNA into the specified genomic target site of an intact animal. Our method uses site-specific cleavage, end-capture of cohesive ends, and obligate ligation-gated recombination. This approach is straight-forward and yields high efficiency without additional gene manipulations; therefore it is easily applicable to a much broader range of organisms. We demonstrate its application to the fungus fly Sciara coprophila where a transformation system has not existed before. We integrated a 6.5 kb transgene precisely at the desired genomic target site of Sciara using this method. This provides the foundation for future experiments to explore the unique genetic features of this organism. Similarly, the method described here will allow insertion of large pieces of DNA into a diverse group of organisms for studies of their genetic attributes.